How does the increase in foreign players affect football? - Sever, Ozan; Ciğerci, Erdem; Öztop, Melih; İpekoğlu, Gökhan; Akyıldız, Zeki; Nobari, Hadi; Gönülateş, Süleyman (Springer Science and Business Media LLC, 2023)
Abstract Background In the study, we tried to analyze the effects of foreign players on Turkish Super League matches. For this purpose, in this long-term study, 1836 competition data played in 6 seasons between 2014 and 2020 was obtained from www.mackolik.com each year. Method Pearson's correlation coefficient applied between 18 different variables (goal, shoot, pass, cross, corner, offside, foul, yellow card, red card, accurate shot, percentage of the precise pass, rate of accurate access on opponent's field, the difference of ball possession percentage, shot difference, pass difference, big team superiority, home team superiority) and the number of foreign players (NoFP, active foreign players in 90 min.). Result In the Turkish Super League, within six seasons (2014–20), the NoFP in a match increased from 10.43 (38.06%) to 17.99 (64.26%). The increment was partially linear and statistically significant (F = 594.85) in all seasons. A positive association was found between NoFP several of passes (r = 0.219), percentage of accurate passes (r = 0.133), percentage of precise passes on the opponent's field (r = 0.139), exact pass difference between opponents (r = 0.114), and ball possession difference between opponents (r = 0.113). Fouls committed decreased with the increase of NoFP (r = -0.250). Although the win probability of the teams named The Big Three (Fenerbahçe, Galatasaray, and Beşiktaş) decreased from 67% (2014 season rate) to 50% in the last two seasons, no association was identified between the NoFP and big team superiority. Conclusions Consequently, NoFP increment may improve the game quality by increasing accurate passes and passes in the opponent's field. The number of passes and the ball possession percentage difference between opponent teams may indicate that one team has control of the game by keeping possession or the other is tactically giving possession. These findings may suggest that the game evolved into half-field, tactical, set-play, possessioning competition. Analyzing variables such as game speed, intensity, the duration of the ball in play, running distance, energy consumption, and fatigue markers may light future studies.
Keywords: Teams; Impact; Football analytics; Research; Football performance; Football statistics; Sports medicine; Foreign players; Nationality; Turkish Super League; RC1200-1245